2013
DOI: 10.1073/pnas.1303317110
|View full text |Cite
|
Sign up to set email alerts
|

Distinct kinetics of synaptic structural plasticity, memory formation, and memory decay in massed and spaced learning

Abstract: Long-lasting memories are formed when the stimulus is temporally distributed (spacing effect). However, the synaptic mechanisms underlying this robust phenomenon and the precise time course of the synaptic modifications that occur during learning remain unclear. Here we examined the adaptation of horizontal optokinetic response in mice that underwent 1 h of massed and spaced training at varying intervals. Despite similar acquisition by all training protocols, 1 h of spacing produced the highest memory retentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 58 publications
7
55
0
Order By: Relevance
“…In Pavlovian eyeblink conditioning, a conditioned response seems to be consolidated in the cerebellar cortex (29)(30)(31)(32). Even in OKR adaptation, a trace of long-term memory remains in the cerebellar cortex as the decrease in the number of PF-PC synapses (33,34), which might represent eye movement trajectory or information on OKR phase (35)(36)(37). Moreover, consolidation of motor memory in general should be investigated in depth from reflex to voluntary movement, particularly in primates including humans.…”
Section: Discussionmentioning
confidence: 99%
“…In Pavlovian eyeblink conditioning, a conditioned response seems to be consolidated in the cerebellar cortex (29)(30)(31)(32). Even in OKR adaptation, a trace of long-term memory remains in the cerebellar cortex as the decrease in the number of PF-PC synapses (33,34), which might represent eye movement trajectory or information on OKR phase (35)(36)(37). Moreover, consolidation of motor memory in general should be investigated in depth from reflex to voluntary movement, particularly in primates including humans.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies also suggest changes in spine density in PCs following cerebellar motor learning (Aziz et al . ; Wang et al . ).…”
Section: Phenotype Of Ip3r1‐deficient Micementioning
confidence: 99%
“…Whereas a close link between spine structural rearrangement caused by synaptic plasticity and learning/memory has been thoroughly studied, particularly in cortical and hippocampal neurons (48,49), a previous study has suggested that spine morphology on distal branches of Purkinje cells is not affected by induction of parallel fiber-Purkinje cell LTD (50). However, recent studies have also demonstrated that cerebellar motor learning decreases spine density in Purkinje cells (8,9). Although a molecular mechanism of spine plasticity in Purkinje cells associated with long-term motor learning is unknown, our findings, at least in part, could provide a potential molecular mechanism that links synaptic inputs to spine structural plasticity in Purkinje cells.…”
Section: Discussionmentioning
confidence: 95%
“…Spine density and morphology of Purkinje cells change significantly during development (3, 4), and morphological abnormalities of spines are closely associated with many neurological disorders (5-7). Recent studies also demonstrated that some forms of training for cerebellar motor learning results in altered spine density in Purkinje cells (8,9). Thus, maintenance of proper spine density and morphology of Purkinje cells is a critical aspect of cerebellar functions.…”
mentioning
confidence: 99%